EXTRACTION OF CAROTENOID PIGMENTS FROM BACTERIA LD07 ISOLATED FROM THE COASTAL WATERS OF DUMAI - Mira Angelina Syah; Ummi Mardhiah Batubara; Irwan Effendi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2026)
Carotenoids are natural pigments with significant potential that are widely synthesized by photosynthetic bacteria. In addition to playing a role in photosynthesis, carotenoids also function as natural antioxidants capable of inhibiting the formation of free radicals and providing protection against oxidative stress. This study aims to characterize and to identify carotenoid pigments synthesized by marine photosynthetic bacteria, to determine the types of pigments, as well as to prove their antioxidant activity. The method used in this study was experimental, conducted to test the ability of marine photosynthetic bacteria to synthesize carotenoid pigments as producers of antioxidant compounds. The results of the study indicate that isolate LD07, a photosynthetic marine bacterium, contains carotenoid pigments. UV-Vis spectrophotometer analysis revealed a maximum absorption peak at a wavelength of 490 nm, a value within the characteristic absorption region of carotenoid pigments